Jovens mulheres, hip-hop, estilo de vida e feminismo - Silva e Freitas, Mara Raissa Santos (2018)
The present research consists of analyzing the meanings of the participation of women related to Hip-Hop in the metropolitan region of Aracaju/SE and aims to understand how women's identities are constructed in this context. Therefore, this theme is inserted in the theoretical field of studies of gender and youths and has as analytical reference the debates related to the identity processes. Considered a contemporary youth movement with great visibility, Hip-Hop has a mostly male audience. However, there is a significant growth of women in rap, graphite or break dance. Through the field research, it was sought to make observations of the activities promoted by five female groups, as well as using two modalities of interviews, one focusing on the trajectories of the possible leaderships of these groups and another with specific themes linked to the gender's relations that also included analyzes on the narratives of three young men. In this way, it was possible to think about the female participation in this culture based on the identifications, discourses and practices that are built in this space, but also to understand how the gender relations and the sociabilities established in the cultural practices around this universe are currently being given.